Use of breast surveillance between women with pathogenic variants and variants of uncertain significance in breast cancer susceptibility genes. Issue 20 (23rd August 2022) - Makhnoon, Sukh; Chen, Minxing; Levin, Brooke; Ensinger, Megan; Mattie, Kristin D.; Grana, Generosa; Shete, Sanjay; Arun, Banu K.; Peterson, Susan K.
Abstract : Background: Use of surveillance mammography and magnetic resonance imaging (MRI) has been understudied among women with variant of uncertain significance (VUS) compared to pathogenic and likely pathogenic variants (P/LP). Methods: Using data from two cancer settings, we calculated use of risk‐reducing mastectomy (RRM) and surveillance during each 13‐month span after genetic testing up to 6 years afterwards for a cohort of genetically elevated risk women. Results: Of 889 women, VUS carriers were less likely to undergo RRM compared to those with P/LP (hazard ratio [HR], 0.17; p = <.001) and high‐risk women were more likely to undergo RRM than average‐risk women (HR, 3.91; p = .005). Longitudinally, surveillance use among unaffected women decreased from 49.8% in the first year to 31.2% in the sixth year after genetic testing. In comparison, a greater proportion of women with a personal history of breast cancer underwent surveillance, which increased from 59.3% in the first year to 63.6% in the sixth year after genetic testing. Mammography rates did not differ between women with P/LP and VUS within the first 13 months after genetic testing and up to 4 years afterward. Over the first 4 years after genetic testing, women with VUS were less likely to undergo annual MRIs compared to P/LP. Conclusion: The authors found that VUS, whether in high or moderate penetrance breast cancer susceptibility genes, was associated with lower use of annual breast MRI compared to P/LP variants and equivalent use of annual mammography. These results add important evidence regarding VUS‐related breast surveillance. Abstract : This study compares the use of breast surveillance between women with variants of uncertain significance (VUS) and pathogenic variants in breast cancer susceptibility genes. The authors find that VUS carriers, both with and without a personal history of cancer, have significantly lower use of annual breast MRI compared to those with pathogenic or likely pathogenic variants, which adds important evidence regarding VUS‐related surveillance.